2008
DOI: 10.1080/15250000802189386
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Infant Person‐ and Object‐Directed Interactions in Latino Immigrant Families: A Comparative Approach

Abstract: Cultural variation in durations, relations, and contingencies of mother–infant person-and object-directed behaviors were examined for 121 nonmigrant Latino mother–infant dyads in South America, Latina immigrants from South America and their infants living in the United States, and European American mother–infant dyads. Nonmigrant Latina mothers and infants engaged in person-directed behaviors longer than Latino immigrant or European American mothers and infants. Mother and infant person-directed behaviors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…In agreement with other studies, we found that mothers were more responsive than infants in person-directed (Bornstein et al, 2011; Cote et al, 2008) and vocal interactions (Van Egeren et al, 2001), meaning that infants influence these kinds of exchanges. Although mothers are the more mature partner in the dyad (Kochanska & Aksan, 2004), these findings highlight the fact that infants also influence mother-infant interactions and mother-infant relationships more generally.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with other studies, we found that mothers were more responsive than infants in person-directed (Bornstein et al, 2011; Cote et al, 2008) and vocal interactions (Van Egeren et al, 2001), meaning that infants influence these kinds of exchanges. Although mothers are the more mature partner in the dyad (Kochanska & Aksan, 2004), these findings highlight the fact that infants also influence mother-infant interactions and mother-infant relationships more generally.…”
Section: Discussionsupporting
confidence: 93%
“…Mothers respond when their infants look at them or vocalize by encouraging social interaction (Bornstein, Cote, Haynes, Suwalsky, & Bakeman, 2011; Bornstein & Manian, 2011; Cote, Bornstein, Haynes, & Bakeman, 2008) and by speaking to the baby (Bornstein & Manian, 2011; Van Egeren et al, 2001). For their part, young infants have been shown to respond to maternal encouragement of social interaction by looking at mother (Bornstein et al, 2011; Cote et al, 2008), and they respond to maternal speech by vocalizing and by looking (Van Egeren et al, 2001). By 5 months of age infants actively participate in turn-taking exchanges (Belsky, Gilstrap, & Rovine, l984; Bornstein & Tamis-LeMonda, 1990; Kaye & Fogel, 1980).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary developmental theories build on this idea by demonstrating the dynamic nature of parental support: Adult caregivers continually adjust their behaviors in line with infants' changing needs and skills (Hirsh‐Pasek & Burchinal, ; Kochanska & Aksan, ). Moreover, mothers from different ethnic and cultural communities have been shown to rely on different behavioral strategies, highlighting the influences of broader sociocultural contexts in mother–child interactions (Bornstein, Cote, Haynes, Suwalsky, & Bakeman, ; Cote, Bornstein, Haynes, Bakeman, ; Kärtner, Keller, & Yovsi, ; Kermani & Brenner, ; Tamis‐LeMonda, Song, Leavell, Kahana‐Kalman, & Yoshikawa, ).…”
Section: Maternal Strategies and Infants' Object‐directed Actions In mentioning
confidence: 99%
“…There is little evidence regarding whether Latin American and African American parents differ from one another on parenting attributions and progressive versus authoritarian attitudes, but in related domains, Latin American parents have sometimes been found to be more similar to European American than African American parents (e.g., Hughes & Kwok, 2007; Zimmerman, Khoury, Vega, Gil, & Warheit, 1995). Furthermore, first-generation Latin American immigrant mothers have been found to interact with their 5-month-old infants in ways that are more similar to the ways that European American mothers interact with their infants than to the ways that mothers from their countries of origin interact with their infants (Cote, Bornstein, Haynes, & Bakeman, 2008). …”
Section: Introductionmentioning
confidence: 99%